Working from home, work-time control and mental health: Results from the Brazilian longitudinal study of adult health (ELSA-Brasil) - Griep, Rosane Harter; Almeida, Maria da Conceição C.; Barreto, Sandhi Maria; Brunoni, André R.; Duncan, Bruce B.; Giatti, Luana; Mill, José Geraldo; Molina, Maria del Carmen B.; Moreno, Arlinda B.; Patrão, Ana Luisa; Schmidt, Maria Inês; Fonseca, Maria de Jesus Mendes da (Frontiers in Psychology, 2022)
This cross-sectional study investigated the association between work-time control (WTC), independently and in combination with hours worked (HW), and four mental health outcomes among 2318 participants of the Longitudinal Study of Adult Health (ELSA-Brasil) who worked from home during the COVID-19 pandemic. WTC was assessed by the WTC Scale, and mental health outcomes included depression, anxiety, stress (measured by the Depression, Anxiety and Stress Scale, DASS-21) and self-rated mental health. Logistic regression models were used to determine odds ratios (ORs) and 95% confidence intervals (CIs). Among women, long HW were associated with stress (OR=1.56; 95% CI=1.11-2.20) and poor self-rated mental health (OR=1.64; 95% CI=1.13-2.38), whereas they were protective against anxiety among men (OR=0.59; 95% CI=0.37-0.93). In both sexes, weak WTC was associated with all mental health outcomes. Among women, the long HW/weak WTC combination was associated with all mental health outcomes, and short HW/weak WTC was associated with anxiety and stress. Among men, long HW/strong WTC was protective against depression and stress, while short HW/strong WTC and short HW/weak WTC was associated with all mental health outcomes. In both sexes, weak WTC, independently and in combination with HW, was associated with all mental health outcomes. WTC can improve working conditions, protect against mental distress, and foster work-life balance for those who work from home.